Evaluation of parallel programming teaching methodologies: On‐campus versus online methodologies - Cantabella, Magdalena; Guillén, Miguel Ángel; López, Belén; Muñoz, Andrés; Cecilia, José M. (Computer applications in engineering education, 2020)
Contribution This study reveals that the programming paradigm is relevant to obtain advanced programming skills. Background Parallel computing has become mandatory for computer science students. The increasing amount of computational resources required by emerging applications need experienced programmers that fully exploit hardware resources. However, the hardware platforms and programming languages to leverage them evolve at a dizzying pace, making very challenging for students the successful learning of the continuously changing high‐performance computing concepts. Research Questions (a) Is the learning curve of the programming language too steep to begin learning parallel programming fundamentals? (b) Are emergent learning methodologies making even more difficult to learn parallel programming in general? Methodology It is analyzed the main challenges for succeeding in parallel programming courses at the undergraduate level in two different learning modalities, namely on‐campus and online. It is analyzed the main tools available within a learning management system, showing their impact on online studies. Findings Our results reveal that the steep learning curve for parallel programming is one of the main barriers to student success, leading to an early drop out of the subject. On‐campus studies mitigate this problem through a close relationship between students and educators. Online studies, however, do not have this tight relationship by its definition.